2011
DOI: 10.1002/dc.21375
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry for the detection of renal cell carcinoma in effusion cytology

Abstract: Renal cell carcinoma (RCC) is known for its unpredictable behavior. RCC rarely involves serosal surfaces and, when present, can be difficult to distinguish from mesothelial cells in cytologic preparations. Immunohistochemical stains are frequently used with effusion cytology; however, RCCs express traditional glandular antigens less frequently than other adenocarcinomas. We investigated the utility of typical immunohistochemical stains for identifying effusion involvement by RCC, along with more specific RCC m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…In a previous study of 11 cases comprising 6 clear cell, 3 papillary, and 2 unclassified RCC, Chute et al 8 reported that MOC-31 applied in cell blocks was negative for all clearcell and unclassified RCC, and positive for 3 papillary RCC. In a previous study of 11 cases comprising 6 clear cell, 3 papillary, and 2 unclassified RCC, Chute et al 8 reported that MOC-31 applied in cell blocks was negative for all clearcell and unclassified RCC, and positive for 3 papillary RCC.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a previous study of 11 cases comprising 6 clear cell, 3 papillary, and 2 unclassified RCC, Chute et al 8 reported that MOC-31 applied in cell blocks was negative for all clearcell and unclassified RCC, and positive for 3 papillary RCC. In a previous study of 11 cases comprising 6 clear cell, 3 papillary, and 2 unclassified RCC, Chute et al 8 reported that MOC-31 applied in cell blocks was negative for all clearcell and unclassified RCC, and positive for 3 papillary RCC.…”
Section: Discussionmentioning
confidence: 97%
“…The nuclear/cytoplasmic ratio varies. 8 While approximately 67% of malignant effusions can be diagnosed with smear preparations, this rate can be increased to 83-85% by applying various immunohistochemical (IHC) markers to the cell blocks. [1][2][3][4] If the malignant effusion is biphasic, neoplastic cells would show contrast with existing benign mesothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…WT1, however, has no utility in discriminating between peritoneal mesotheliomas and serous carcinomas of the ovary and peritoneum because the latter tumors have been reported to be positive for this marker in most cases (83%-100%) [57,[59][60][61][62]. Only a few studies have investigated the expression of WT1 in renal cell carcinomas, and they have shown that this marker is rarely expressed in these tumors [27,57,63]. In an investigation by this author, only 1 (4%) of 24 clear cell renal cell carcinomas and none of the papillary, chromophobe, or sarcomatoid renal cell carcinomas included in that study were WT1 positive [27].…”
Section: Wt1 Proteinmentioning
confidence: 95%
“…Only a few studies with a relatively small number of cases have been published on WT1 expression in renal cell carcinomas. 10,102,104,105 In the largest of these studies, which was by this author, WT1 positivity was demonstrated in only 1 (4%) of 24 clear cell, but in none of 8 papillary or 12 chromophobe, renal cell carcinomas included in that investigation. 10 Mesothelin is a marker that has been reported to be commonly expressed in epithelioid mesotheliomas (B90-100%).…”
Section: Discussionmentioning
confidence: 77%